Non-Orthogonal Multiple Access Technology for 5G Systems - Qi Bi; Lin Liang; Shan Yang; Peng Chen (Dianxin kexue)
To meet the 5G requirements on spectral efficiency and number of connections，non-orthogonal multiple access（NMA）technology is becoming an important candidate technology.It was shed light on how NMA can be used to further improve spectral efficiency over OMA，in order to achieve the multiple user channel capacity.Detailed analysis were given on the design principle，signal processing and resultant performance gain of three typical NMA schemes including power-domain，constellation-domain and code-domain NMA.Furthermore，network operating aspects for NMA like deployment scenarios，system design impact as well as network backward compatibility were presented.